Interpretation According To Jurisprudents - Kana'n Mustafa Sai'd Shatat (My University, 2007)
There is no doubt that this religion is valid for every time and place. Consequently, its religious discourse occurred in comprehensive way, carrying many meanings and possibilities in a form which comprises all of the incidents of Life until the Day of Resurrection. This discourse is not confined to clarifying the rules and meanings out of the texts through their superficial meaning. Instead, it surpasses this to encompass the interpretation, explanation and others. Moreover, the religious discourse depends on evidence from the holy Koran, Sunna, consensus, measurement and the legislative rationale out of the text, the juristic or fundamental rules and others. The basic aim for the interpretation in the religious discourse is to point out the legislator's intention, because he is too exalted for frivolity, as well as confirming the correctness of this discourse, and applying it according to the circumstances and conditions of living. It should be borne in mind that the multiplicity of the possibilities and meaning for the religious discourse and the divergence of the interpreters' views have a prominent effect in most of the subsidiary juristic issues as well as all the branches and specifications of this religion according to the interpretation and understanding of each interpreter for the evidence. Despite these differences resulting from the diversity of the understanding of each interpreter, they were not completely incompatible. This confirms the correctness of saying that this religion is completely in harmony with its parts without contradiction.

لا يماري ممار في أن هذا الدين يصلح لكل زمان ومكان وعلى هذا الأساس فقد جاء معظم الخطاب القرآني فيه بطريقة كلية ومجملة، ثم كان الخطاب فيه حاملاً لكثير من المعاني والاحتمالات بحيث شمل جميع حوادث الحياة حتى قيام الساعة. ولم يقتصر هذا الخطاب على بيان الأحكام والمعاني من النصوص من خلال ظاهرها بل تعداه إلى التأويل والتفسير وغيرها وكان يستند إلى الدليل من الكتاب السنة والإجماع والقياس والحكمة التشريعية من النص والقواعد الفقهية أو الأصولية وغيرها. وكان الهدف الرئيس من وراء التأويل في الخطاب الشرعي بيان مراد الشارع ومقصوده فيه لأن الشارع منزه عن اللعب والعبث، وتحقيق صدق هذا الخطاب وتنزيله على الواقع حسب الظروف والأحوال المعاشة. ولا يفوتني القول إن تعدد الاحتمالات والمعاني للخطاب الشرعي واختلاف المتأولين له ذو أثر بالغ في أغلب المسائل الفقهية الفرعية منها والجزئية، وفي كافة فروع وجزئيات هذه الشريعة، تبعاً لاجتهاد وتأويل وفهم كل منهم حسب الدليل. ورغم هذه الاختلافات الناتجة عن اختلاف فهم كل متأول إلا أنها لم تكن متعارضة بشكل كلي مما يؤكد على صحة القول بأن هذه الشريعة منسجمة تمام الانسجام ومتفقة تمام الاتفاق مع بعضها البعض دون تعارض فيها.
التأويل عند الأصوليين